Analisis Ungkapan Persuasif Pada Lirik Lagu Ebiet G.Ade Sebagai Materi Pembelajaran Bahasa Indonesia Di Smk - Destiyani, Rina Wahyu, Prof. Dr. Abdul Ngalim, M.M.,M.Hum (2016)
This study has three objectives. (1) Describe the form of the use of persuasive expression in the song lyrics Ebiet G.Ade, (2) describe the contents of the message contained in the lyrics Ebiet G.Ade, (3) describe the use of persuasive expression as a form of use of the learning materials at SMK. This research uses a qualitative method. The methods used in data collection is a method refer to. Furthermore, this technique followed by an advanced technique that is noted techniques. Methods of data analysis using intralingual match and unified referential. There are six things worth discussed in this study. (1) The expression persuasive that it is an invitation, (2) the recommendation, (3) command, (4) advice, (5) asserted, and (6) the wise. The contents of the message contained in the lyrics Ebiet G.Ade a description or sentences poet to listeners who aim to influence the listener. Persuasive form of use of the phrase in the song lyrics Ebiet G.Ade can be used as material and examples of teaching in schools, particularly in the vocational school.